EKSISTENSI TOKOH PEREMPUAN DALAM DONGENG SNEEWITTCHENKARYA GRIMM BERSAUDARADevi Ambarwati PuspitasariProgram Pasca SarjanaUniversitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
Abstract Sneewittchen story by Grimm brother is a story that focuses on women characters. To reveal the existence of women in the story, Existentialism; a theory by Jean Paul Satre is used in the analysis. The form of existence in this story is Atheis existent. Sneewittchen character is the depiction of threatening forms to the beauty and immortality of her step mother (die Königin). These threatening need to be destroyed by killing Sneewittchen. In Atheis existent, killing is permitted in the sense of keeping one’s existence.Keywords: evil, threatening forms, freedom